Periodic Solutions of the Forest Pest System Via Hopf Bifurcation and Averaging Theory - Othman, Kardo Baiz; Amen, Azad Ibrahim (Iraqi Journal of Science, 2022)
This work aims to analyse the dynamic behaviours of the forest pest system. We confirm the forest pest system in plane for limit cycles bifurcating existence from a Hopf bifurcation under certain conditions by using the first Lyapunov coefficient and the second-order of averaging theory. It is shown that all stationary points in this system have Hopf bifurcation points and provide an estimation of the bifurcating limit cycles.